2017
DOI: 10.13057/biodiv/d180123
|View full text |Cite
|
Sign up to set email alerts
|

Spore germination and early gametophyte development of Platycerium wandae (Polypodiaceae) from Papua, Indonesia

Abstract: Abstract. Hapsari L, Kennedy J, Lestari DA, Masrum A, Lestarini W. 2017. Ethnobotanical survey of bananas (Musaceae) in six districts of East Java,. Ethnobotanical survey of bananas was conducted in six districts of East Java, Indonesia i.e. Pasuruan, Probolinggo, Banyuwangi, Lumajang, Jember and Malang during 2012-2015. Seventy-nine local cultivar names were recorded in the six districts, including local Javanese names and some possible synonyms among the cultivars. Four genomic groups are represented: AA (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 62 publications
2
5
0
Order By: Relevance
“…The dealing patterns between men (husbands) and women (wives) roles in the farmer families are inseparable regarding the palm sugar management and exploitation in daily routinely. The same thing was found by Hapsari et al (2017) in six districts in East Java the majority of men were found working in agriculture during the day, while women were at home. Puspitawati et al (2018) state that in general, gender roles in agricultural activities, in terms of access and control of agricultural resources, are dominated by men.…”
Section: Farmers Characteristics Gendersupporting
confidence: 74%
“…The dealing patterns between men (husbands) and women (wives) roles in the farmer families are inseparable regarding the palm sugar management and exploitation in daily routinely. The same thing was found by Hapsari et al (2017) in six districts in East Java the majority of men were found working in agriculture during the day, while women were at home. Puspitawati et al (2018) state that in general, gender roles in agricultural activities, in terms of access and control of agricultural resources, are dominated by men.…”
Section: Farmers Characteristics Gendersupporting
confidence: 74%
“…However, various tribes and dialects have been added more confusion to proper identification and documentation not only in Indonesia but also in other countries with a high diversity of banana (Atom et al 2015). Cultivar names are given by local community sometimes have reflected distinct morphological characteristics like smell and taste and ease us to differentiate specific banana among banana cultivars (Hapsari et al 2017). However, various tribes and dialects have generated different names in the same banana cultivars.…”
Section: Cluster Analysis Using Morphological Charactersmentioning
confidence: 99%
“…In Indonesia, M. balbisiana has some miscellaneous uses. Hapsari et al (2017) reported that local people in Java, particularly in East Java used leaves for wrapping and medicinal use, immature fruit and male bud were for consumption, and fruit was used as medicine. Leaves of M. balbisiana are preferred as wrapper because they were thick, wide, and were not easily torn.…”
Section: Musa Balbisiana Collamentioning
confidence: 99%